NEED FOR CONSIDERING DIFFERENT MODES OF LEARNING IN JOHN LEE HANCOCK’S THE BLIND SIDE MOVIE (2009): AN EDUCATIONAL PSYCHOLOGICAL PERSPECTIVE - ARDIYANTO , ANGGA (2011)
This study is aimed to show the different learning style that the major character has by using educational psychology. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the seconds is analyzing the movie based on the psychological analysis.